2000
DOI: 10.1002/(sici)1096-9071(200004)60:4<367::aid-jmv2>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The NS5a gene of hepatitis C virus in patients treated with interferon-?

Abstract: Patients infected with hepatitis C virus (HCV) genotype 3 have a better response to interferon-alpha (IFN-alpha) therapy than those infected with genotype 1. There are extensive sequence differences between genotypes in the 3' half of the NS5a gene. An association between IFN-alpha response and the interferon sensitivity-determining region (ISDR) (amino acids 2209-2248) of HCV genotype 1b has been described [Enomoto et al. (1996) New England Journal of Medicine 334:771-776]. A prospective study was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…These data further support the concept that both viral load and degree of complexity independently affect viral clearance, as reflected by both RVR and SVR. Identification of specific HCV signature motifs that are more or less prone to early clearance may improve our understanding of mechanisms of interferon resistance, though other groups have found it difficult to reliably identify such motifs[23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…These data further support the concept that both viral load and degree of complexity independently affect viral clearance, as reflected by both RVR and SVR. Identification of specific HCV signature motifs that are more or less prone to early clearance may improve our understanding of mechanisms of interferon resistance, though other groups have found it difficult to reliably identify such motifs[23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in several studies from Japan, Europe, and the United States, the observed correlation of ISDR mutations and treatment outcome was verified. However, mainly Japanese groups were able to obtain concordant results Komatsu et al, 1997;Chayama et al, 1997) whereas in Europe and the United States, initially no such association was detected for HCV genotype 1b infected patients (Zeuzem et al, 1997;Khorsi et al, 1997;Squadrito et al, 1997;Odeberg et al, 1998;Chung et al, 1999;Hofgartner et al, 1997;McKechnie et al, 2000). Studies from Western countries based on larger patient cohorts and, more recently, results of a metaanalysis could confirm an association of ISDR mutations and treatment outcome.…”
Section: Significance Of Amino Acid Exchanges Within Different Hcv Rementioning
confidence: 95%
“…Studies from Japan were generally able to confirm the strong correlation between ISDR mutations and treatment response (16,69). Groups from Europe and the United States were initially not able to verify the importance of ISDR mutations in IFN-␣ sensitivity (18,65,84,99,133,154), and in subsequent studies, it turned out that HCV genotype 1b isolates with multiple mutations within the ISDR are rare in Europe and the United States compared to those found in Japan (104,117,121,122). In further studies with larger patient cohorts and in a meta-analysis, the positive correlation of an increasing number of ISDR mutations with a sustained virologic response to IFN-␣-based therapy could be confirmed (102,104,117,121,122).…”
Section: Vol 20 2007 Resistance To Treatment In Patients With Hcv 27mentioning
confidence: 99%